Sistem Panel Kinerja Untuk Program Studi Sarjana Berbasis BAN PT - Utomo, Agus Prasetyo; Mustafid, Mustafid; Widiyanto, Ibnu (JSINBIS (Jurnal Sistem Informasi Bisnis), 2013)
Study program need to do monitoring and continuously measurements of performance to ensure achievement the goals set of its. The process of performance requires monitoring data and information was taken from all parts of the organization. The purpose of this research is to build a panel system performance (performance dashboard) that can be used to help measure the performance of undergraduate degree courses based on BAN PT in order of quality assurance in higher education. The results of performance monitoring will be delivered to the parties concerned, efficiently and effectively. Panel System (Dashboard) is a tool to present information at a glance. Dashboard inform using Key Performance Indicators (KPI) an effective presentation media. KPIs are used in the construction panel system performance of these courses entirely using the instruments of the National Accreditation of Higher Education. The methodology can be applied either on a case study of the development of dashboards to support the efforts of quality assurance courses at the Stikubank University Semarang. This study emphasizes how the application is to provide easy information to Head of study program, Dean of faculty, Rector and Vice Rector of university to the achievement of the quality of undergraduate study program. Â  Keywords: Performance Dashboard; Key Performance Indicators; Accreditation.